F-spondin Is Essential for Maintaining Circadian Rhythms - Carrillo, Gabriela L.; Su, Jianmin; Monavarfeshani, Aboozar; Fox, Michael A. (Frontiers in Neural Circuits, 2018)
The suprachiasmatic nucleus (SCN) is the master pacemaker that drives circadian behaviors. SCN neurons have intrinsic, self-sustain rhythmicity that is governed by transcription-translation feedback loops. Intrinsic rhythms within the SCN do not match the day-night cycle and are therefore entrained by light-derived cues. Such cues are transmitted to the SCN by a class of intrinsically photosensitive retinal ganglion cells (ipRGCs). In the present study, we sought to identify how axons from ipRGCs target the SCN. While none of the potential targeting cues identified appeared necessary for retinohypothamic innervation, we unexpectedly identified a novel role for the extracellular matrix protein F-spondin in circadian behavior. In the absence of F-spondin, mice lost their ability to maintain typical intrinsic rhythmicity. Moreover, F-spondin loss results in the displacement of vasoactive intestinal peptide (VIP)-expressing neurons, a class of neurons that are essential for maintaining rhythmicity among SCN neurons. Thus, this study highlights a novel role for F-spondin in maintaining circadian rhythms.